The intervention effect of physical and mental exercise on young adults internet addiction disorder: a systematic review and Bayesian model analysis - Jia, Shiguan; Wang, Hao; Chu, Dengshan; Yao, Jiayi; Wang, Haozhe; Chen, Wenjia; Zhang, Dazhong; Zhang, Wenzhong (Frontiers in Public Health, 2025)
BackgroundAs a behavioral addiction, internet addiction disorder has become a global problem that seriously affects people’s mental health. Although physical and mental exercise is believed to help alleviate related symptoms, there is currently a lack of systematic research evaluating the intervention effects of different physical and mental exercises on internet addiction disorder.ObjectiveTo systematically evaluate the effects of different physical and mental exercise modes and amounts on the alleviation of symptoms of internet addiction.MethodRandomized controlled trials (RCTs) on the effects of different physical and mental exercise modes on internet addiction published between October 2000 and February 2025 were retrieved through PubMed, Web of Science, EBSCO, Cochrane Library, and CNKI systems. After independently screening literature, extracting data, and evaluating the risk of bias in the included studies by two independent researchers, a random effects model was used for meta-analysis using RevMan 5.4 and Stata 19.0 software. Perform dose-response analysis using R software.ResultsTwenty-four randomized controlled trials involving 1,711 participants were included. Compared with the control group, all physical and mental exercise methods significantly improved symptoms of internet addiction disorder (SMD = −1.63, 95% CI: −2.04, −1.22). Mindfulness meditation showed the strongest effect (SMD = −2.04, 95% CI: −3.23, −0.85). The study determined a non-linear U-shaped dose-response relationship, with the best effect occurring at 730 MET min/week.ConclusionThis study provides theoretical support for non pharmacological interventions to improve symptoms of internet addiction disorder. For those who hope to improve their internet addiction through physical and mental exercise, mindfulness meditation is the first choice. In addition, controlling the exercise dose within the optimal range (e.g., 730 MET min/week) can significantly enhance the intervention effect.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025631096, CRD42025631096